China - art - modernity a critical introduction to Chinese visual expression from the beginning of the twentieth century to the present day - Clarke, David J. 1954- (HKU Press, 2019)
Provides a critical introduction to modern and contemporary Chinese art as a whole. It illuminates what is distinctive and significant about the rich range of art created during the tumultuous period of Chinese history from the end of Imperial rule to the present day. The story of Chinese art in the twentieth and twenty-first centuries is shown to be deeply intertwined with that of the country's broader socio-political development, with art serving both as a tool for the creation of a new national culture and as a means for critiquing the forms that culture has taken. The book's approach is inclusive. In addition to treating art within the Chinese Mainland itself during the Republican and Communist eras, for instance, it also looks at the art of colonial Hong Kong, Taiwan and the Chinese diaspora. Similarly, it gives equal prominence to artists employing tools and idioms of indigenous Chinese origin and those who engage with international styles and contemporary media.